Growth Response and Production Kind of Sweet Potato Varieties (Ipomoea batatas (L.) Lam) by giving Rice Straw Compost - ANDI SYAHPUTRA; Nini Rahmawati; Hot Setiado (Jurnal Agroekoteknologi, 2017)
The research was carried out at public land Desa Namo Gajah, Kecamatan Medan Tuntungan(±25 m dpl) on April to November 2015. The research used factorial Randomized Block Design (RBD) with two factors and three replications.The first factor was sweet potato varietieswith 3 kinds (Antin-1; Beta-1; and Sari)and the second factorwas rice straw compost with 4 levels(0; 5; 10; and 15 ton/ha). Data were analized with Analysis of Variance and continued with Duncan’s Multiple Range Test (DMRT). The variables observed weight biomass of plant, tuber weight per plot, and harvest index. The result of research showed that the best interaction of sweet potato varieties and rice straw compost was combination of Sari and rice straw compost 2 kg on weight biomass, tuber weight per plot, and harvest index.